Does fungal infection is the main cause for persistent middle ear otorrhea? - Mohamad, Hazama; Md Daud, Mohd Khairi; Hasan, Habsah; Wong, Chun Yiing (Elsevier, 2017)
Objectives: Chronic suppurative otitis media commonly caused by bacterial infection however with the commencement of antibiotics, the otorrhea would always resolved within a short period of time. The aim of this study was to look at the involvement of fungus in CSOM with persistent otorrhea and association between topical antibiotic eardrop with fungal infection in CSOM. Methods: Sixty-two patients were included in this cross sectional study which was carried out in Otorhinolaryngology clinic Hospital Universiti Sains Malaysia. All CSOM patients with persistent otorrhea for at least two weeks were included in this study. Patient with otomycosis, intact tympanic membrane, otitis externa and cholesteatoma were excluded from the study. The swab samples for bacterial and fungal culture were collected under aseptic precautions. Ofloxacin eardrop were prescribed to all patients for two weeks. The patients were advised to strictly clean the ear canal before applying the ear drops and to keep the ear dry. After two weeks, if there were persistent ear discharge, swab for fungal culture and bacterial study were repeated. Results: The incidence of fungal infection was 6.4% (4/62). The fungi isolated were Aspergillus, Candida and Penicillium species. Majority cases of otorrhea cultured bacteria. There was no association of fungal infection and topical antibiotics instead we found ofloxacin to be an effective medication in treating otorrhea. Conclusion: The incident of fungal colonization in persistent otorrhea is low (7%). The fungal isolated were Aspergillus flavus, Candida parapsilosis and Penicillium spp. Bacteria are still the most common microorganism in persistent otorrhea.